Genotyping and Whole-Genome Sequencing to Identify Tuberculosis Transmission to Pediatric Patients in British Columbia, Canada, 2005–2014. (11th May 2018) - Guthrie, Jennifer L; Delli Pizzi, Andy; Roth, David; Kong, Clare; Jorgensen, Danielle; Rodrigues, Mabel; Tang, Patrick; Cook, Victoria J; Johnston, James; Gardy, Jennifer L
Abstract : Retrospective genotyping and whole-genome sequencing over a 10-year period suggested that pediatric tuberculosis in British Columbia is a mosaic and factors including age, birthplace, and travel history must all be considered together when inferring a pediatric patient's likely exposure. Abstract: Background: Tuberculosis (TB) in children is often an indicator of recent transmission. Genotyping and whole-genome sequencing (WGS) can enhance pediatric TB investigations by confirming or refuting transmission events. Methods: Mycobacterium tuberculosis isolates from all pediatric patients <18 years with culture-confirmed TB in British Columbia (BC) from 2005 to 2014 ( n = 49) were genotyped by Mycobacterial Interspersed Repetitive Units–Variable Number Tandem Repeat (MIRU-VNTR) and compared with adult isolates. Genotypically clustered cases underwent WGS. Clinical, demographic, and contact data were reviewed for each case. Results: Twenty-three children were Canadian-born, 7 to Canadian-born parents (CBP) and 16 to foreign-born parents (FBP). Of the 26 foreign-born children, all were born in Asia (81%) or Africa (19%). Using molecular and epidemiological data, we determined that 15 children had acquired their infection within BC, and household transmission explained all 7 Canadian-born (FBP) children that acquired TB locally. In contrast, 6 of 7 Canadian-born (CBP) children were exposed via a non-household community source. Eight Canadian-born (FBP) children acquired their infections through travel to their parents' place of birth. All but 1 of the foreign-born children acquired their infection outside of BC. Conclusions: Genotyping and genomic data reveal that drivers of pediatric transmission vary according to a child's age, birthplace, and their parents' place of birth.